KEGIATAN EKSTRAKURIKULER TARI PIRING DI SMP NEGERI 26 PADANG (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the extracurricular Plate Dance activities at SMP Negeri 26 Padang. This type of research is qualitative with a descriptive method. The research instrument is the researcher themselves, assisted by supporting instruments such as stationery and a camera. Data was collected through literature study, observation, interviews, and documentation. The steps of data analysis were carried out through data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the extracurricular Plate Dance activities at SMP Negeri 26 Padang have been carried out well according to the training program prepared by the supervisor. The activity planning includes setting activity goals, preparing a training program, determining the training schedule, providing facilities and infrastructure, and determining the students and supervisors involved. The training was carried out gradually through the introduction of the Plate Dance, exercises in movement variations I, II, and III, repetition of movements, and evaluation before the performance. The extracurricular activity is held once a week, every Friday after classes is over. The factors supporting this activity are the active role of the instructor, the enthusiasm of the students, and the availability of adequate facilities and infrastructure. The obstacles found were differences in students' abilities in mastering the Plate Dance movements. Based on the evaluation results, the students' abilities improved at each meeting, allowing them to perform the Plate Dance well during school performances.